The Pengaruh Konseling Keluarga Berencana Di Pmb Diah Palupi Terhadap Pemilihan Metode Kontrasepsi Di Desa Sukowono Kecamatan Sukowono - Alfitri, Rosyidah; Istifaroh (Jurnal Kesehatan, 2025)
Contraception is an action or method used to delay pregnancy, either temporarily or permanently. This study aims to determine the effect of family planning counseling on contraceptive method choice in Sukowono Village, Sukowono District. The background of this study is based on the important role of counseling in providing understanding to fertile couples in selecting effective contraceptive methods. This study used a quasi-experimental design with a pretest-posttest control group. The sample included 30 postpartum women: the experimental group received family planning counseling, while the control group did not. The sampling included all subjects who met the inclusion criteria. Since the Shapiro-Wilk test showed the data were not normally distributed, the Wilcoxon Signed Rank Test was used for analysis. The analysis indicated a significant difference between the pretest and posttest results in the intervention group (p=0.001), while the analysis of the absence of a difference in the control group indicated a significant difference (p=0.564). The results of family planning counseling at Traik concluded that it significantly influenced changes in decisions regarding contraceptive method selection. It can be concluded that family planning counseling significantly influenced the decision-making process for postpartum mothers at PMB Diah Palupi Sukowono.